Accelerated Transmission Development For Accelerated Power Development (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Due to our lack of vision, planning and other mistakes, Nepal is in a very serious situation of load shedding. The nation is about 200 MW deficit of power supply. Hydropower development is an endeavor related with several sectors. It cannot be taken as only a commercial sector considering that businessmen will make all necessary things when there is a demand. In the past, the transmission sector has not been given due importance. Because of the complex nature of Transmission, there should only be one transmission operator in the country. Based on the periodic basin-wise generation plan of the nation, we should prepare an accelerated Development Plan. The Basin Plan should indicate how and where local level, regional level and national level hydro plants will be connected to the grid, and the sequence of developing the basin transmission network.Hydro Nepal: Journal of Water, Energy and Environment Issue No. 4, January, 2009 Page 8-10